Cytokine and angiogenic factors associated with efficacy and toxicity of pazopanib in advanced soft-tissue sarcoma: an EORTC-STBSG study - Sleijfer, Stefan; Hohenberger, Peter (British journal of cancer, 2012)
Background:Pazopanib has activity in relapsed non-adipocytic soft-tissue sarcomas (STS). A series of serum cytokines and angiogenic factors (CAFs) at baseline and changes in soluble vascular endothelial growth factor receptor-2 (sVEGFR2) or placental-derived growth factor (PlGF) levels during treatment were explored for their association with outcome.Methods:Twenty-three baseline CAFs, and sVEGFR2 and PlGF changes were measured in 85 and 32 patients, respectively. Associations between baseline CAF levels and efficacy parameters, plus between-week 12 sVEGFR2 and PlGF levels and pazopanib-specific toxicities were investigated.Results:At baseline, low interleukin (IL)-12 p40 subunit and MPC3 levels were associated with better progression-free survival (PFS) at 12 weeks (PFS12wks), low basic nerve growth factor and hepatocyte growth factor with a better PFS, and low inter-cellular adhesion molecule-1 and IL-2 receptor alpha with prolonged overall survival (OS; all P<0.05). Pazopanib decreased sVEGFR2 and increased PlGF levels. Low sVEGFR2 and high PlGF levels at week 12 were associated with higher-grade hypertension, with TSH elevations and with poorer PFS12wks, and OS (both P<0.05).Conclusion:Several baseline CAFs were related to outcome parameters. Low sVEGFR2 and high PlGF at week 12 associate with several pazopanib-specific toxicities and poorer efficacy. If confirmed, these factors may be used as early markers for response to and toxicity from pazopanib, enabling further individualisation of STS treatment.